The more empowered schools, the more fruitful students - Kurudirek, Abdullah; Berdieva, Oygul (ARKA INSTITUTE, 2024)
This study emphasizes the importance of adding life skills education to school curricula, recognizing that not all students' paths will lead to traditional employment. While not all students will become doctors, engineers, or lawyers, they will all go through a process of growth. Every individual needs key life skills necessary for resilience, adaptation, and effective management of daily life. This study aims to explore the important role of education in preparing the developing generation to live at the desired level by emphasizing the importance of empowering schools to shape a more productive future. This study utilizes the case study research approach. In this technique, researchers remain outside of the situation under investigation, focusing on the examination of many aspects and components that may interact. as a result, a holistic education, active families, and a developing curriculum with 21st-century skills enable children to overcome social barriers and prepare them for postsecondary education and the workforce. This study proposes a holistic strategy that emphasizes life skills alongside academic coursework, developing individuals who are adaptable and ready to face future challenges by revisiting the traditional educational tripod.